Menerapkan Kemampuan Kecerdasan Logis-Matematis Anak Usia Dini Melalui Permainan Ular Tangga (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
This research aims to explore the application of mathematical logical intelligence abilities in early childhood through the game snakes and ladders. This research us-es a literature review method to examine the application of early childhood mathe-matical logical intelligence abilities through the snakes and ladders game in children and the influence of the game in improving mathematical skills, including number recognition, counting skills, and strategic decision making. The research results show that the snakes and ladders game is effective in stimulating children's cogni-tive, social and motoric development. Apart from that, this game also encourages social interaction and cooperation among children, while making the learning pro-cess more fun and interesting. This research recommends the use of the snakes and ladders game as an innovative and fun educational tool to support children's holistic development, as well as to create a positive and interactive learning atmos-phere